The chemistry of nitrogen oxides on small size-selected cobalt clusters, Co(n) (+). - Anderson, M; Lacz, A; Drewello, T; Derrick, P; Woodruff, D; Mackenzie, S (2009)
Fourier transform ion cyclotron resonance mass spectrometry has been employed to study the reactions of gas-phase cationic cobalt clusters, Co(n) (+) (n=4-30), with nitric oxide, NO, and nitrous oxide, N(2)O, under single collision conditions. Isolation of the initial cluster permits detailed investigation of fragmentation channels which characterize the reactions of all but the largest clusters studied. In reaction with N(2)O, most clusters generate the monoxides Co(n)O(+) without fragmentation, cobalt atom loss accompanying only subsequent reactions. By contrast, chemisorption of even a single NO molecule is accompanied by fragmentation of the cluster. The measured rate coefficients for the Co(n) (+)+N(2)O reaction as a function of cluster size are significantly smaller than those calculated using the surface charge capture model, while for NO the rates are comparable. The reactions have been studied under high coverage conditions by storing clusters for extended periods to permit multiple reactions to occur. This leads to interesting chemistry on the surface of the cluster resulting in the formation of stable oxide clusters and/or the decomposition of nitric oxide on the cluster with the resulting loss of molecular nitrogen.